2012
DOI: 10.1159/000335869
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Improves Cerebrovascular Reserve Capacity by Enhancing Collateral Growth in the Circle of Willis

Abstract: Background and Purpose: Restoration of cerebrovascular reserve capacity (CVRC) depends on the recruitment and positive outward remodeling of preexistent collaterals (arteriogenesis). With this study, we provide functional evidence that granulocyte colony-stimulating factor (G-CSF) augments therapeutic arteriogenesis in two animal models of cerebral hypoperfusion. We identified an effective dosing regimen that improved CVRC and stimulated collateral growth, thereby improving the outcome after experimentally ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 74 publications
(56 reference statements)
1
33
0
1
Order By: Relevance
“…Citicoline treatment decreased neuronal apoptosis and promoted endogenous cerebral repair [80]. A well-known experimental study conducted at Madrid’s Complutense University demonstrated that treatment with citicoline 24 h after MCA occlusion in rats produced an increase in neuronal synaptic spines with increased motor and functional recovery in treated animals [50].…”
Section: Citicoline and Brain Neurorepairmentioning
confidence: 99%
“…Citicoline treatment decreased neuronal apoptosis and promoted endogenous cerebral repair [80]. A well-known experimental study conducted at Madrid’s Complutense University demonstrated that treatment with citicoline 24 h after MCA occlusion in rats produced an increase in neuronal synaptic spines with increased motor and functional recovery in treated animals [50].…”
Section: Citicoline and Brain Neurorepairmentioning
confidence: 99%
“…We assessed DEP-1 deficiency in a mouse model [25] capable of inducing cerebral arteriogenesis by CCAO. In order to be able to detect either a positive or a negative impact on collateral growth due to loss of DEP-1, day 7 after operation was chosen as a read-out for collateral growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral hypoperfusion was induced by unilateral permanent left common carotid artery occlusion (CCAO), as previously described [25]. Cerebrovascular architecture was determined 7 days after operation after maximal vasodilation with 1 mg/kg adenosine using a modified postmortem latex perfusion [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] This therapy has several advantages over traditional treatments such as aspirin and thrombolytic agents because the therapy is less invasive, relatively safe, ethically acceptable, and has a wider therapeutic window. 31 Similarly, well-tolerated administration, feasible treatment regimen, and improved neurologic outcomes have been reported in the individual studies.…”
Section: Summary Of Findingsmentioning
confidence: 99%